Outcome of Laparoscopic Ventral Hernia Repair in a Tertiary Centre: A Descriptive Cross-Sectional Study - Shrestha, Binod Bade; Mishra, Sushil; Shrestha, Sujan; Ghimire , Pradeep; Raj Pandey, Mrigendra (Nepal Journal of Medical Sciences, 2025)
Introduction: Laparoscopic ventral hernia repair (LVHR) is commonly performed at various centers as preferred method for ventral hernia repair. LVHR provides symptom relief and/or hernia resolution while minimizing recurrence rates. This study aimed to evaluate outcomes of LVHR in a tertiary center. Methods: This observational study was conducted in Department of Surgery at Manipal Teaching Hospital, Pokhara, Nepal, from April 1, 2022, to February 28, 2025, following approval from Institutional Review Board (MCOMS/IRC/503/GA). A total of 138 patients were included in study. All laparoscopic hernia repairs (IPOM, IPOM PLUS, SCOLA, TRAM) were performed using three reusable access ports. Patients were discharged on third postoperative day and followed up at one, three, and six months to assess immediate and late complications. Convenience sampling was employed, and data analysis was conducted using SPSS (version 21.0), with a significance level set at p < 0.05. Results: The average age of participants was 51.23±14.81 years, consisting of 75 males (54.3%) and 63 females (45.7%). The median surgical duration was 60 minutes (IQR: 50-85 minutes). Among 138 patients with ventral hernia, 66.7% (92 patients) had primary hernias, 33.3% (46 patients) had incisional hernias. The surgical technique most commonly employed was IPOM plus, performed in 131 instances (94.9%). A total of 11 patients (7.97%) encountered complications, with seroma being most common at 4 occurrences (2.9%), followed by surgical site infection in 2 instances (1.4%). Iatrogenic bowel perforation occurred in 1 case (0.7%), ileus in 1 case (0.7%), recurrence in 1 case (0.7%), mesh infection in 1 case (0.7%), and left iliac fossa ecchymosis in 1 case (0.7%). There was no statistically significant difference in complication rates between primary and incisional hernias (p=0.18). Conclusions: LVHR represents a safe and effective surgical approach for ventral hernia repair, exhibiting minimal complication rates, which aligns with findings from similar studies.